Educação antirracista utilizando a sociologia através das questões s do ENEM - Soares, Raimundo Danúbio Maciel (2024)
In this work I present and analyze an anti-racist pedagogical intervention. It is a sequence of classes held for six months, divided into six modules, in which themes from the Sociology curriculum are developed, accompanied by ENEM questions related to the theme of ethnicracial relations. Especially issues that facilitate the promotion of pedagogical actions aimed at recognizing the identity, origins, culture of black Brazilians and that produce criticism in relation to the legacy of Brazilian history. As part of the activities, we ask the students to evaluate the questions worked on, listing the themes and the degree of difficulty, so that they have feedback in the pedagogical field to analyze how the content is being developed, creating a convergence between what was proposed and the perspectives understanding of students. To theoretically support the creation of the intervention, a legislative, curricular and bibliographical research was carried out on the anti-racist struggle in the field of education and the school curriculum. In terms of didactic-pedagogical inspiration, we follow the model proposed by Gasparin, 2002, in A didactic for historical-critical pedagogy. At the end of the work, we hope to engage students with discussions, concepts and theories in a critical way so that they can autonomously choose an anti-racist stance